Creating Cultural Safety in Couple and Family Therapy Supervision and Training - Allan, Robert; Singh Poulsen, Shruti (AFTA SpringerBriefs in Family Therapy, 2017)
XX, 104 p. 2 illus., 1 illus. in color.